2019
DOI: 10.4254/wjh.v11.i2.217
|View full text |Cite
|
Sign up to set email alerts
|

Parallel transjugular intrahepatic portosystemic shunt with Viatorr® stents for transjugular intrahepatic portosystemic shunt insufficiency: A case report and review of literature

Abstract: BACKGROUND Transjugular intrahepatic portosystemic shunts (TIPS) can alleviate complications of portal hypertension such as ascites and variceal bleeding by decreasing the portosystemic gradient. In limited clinical situations, parallel TIPS may be only solution to alleviate either variceal bleeding or ascites secondary to portal hypertension when the primary TIPS fails to do so. Data specifically addressing the use of this partially polytetrafluoroethylene covered nitinol stent (Viatorr … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 32 publications
(32 reference statements)
1
10
0
Order By: Relevance
“…(Dabos et al 1998 ) Parallel TIPS has since been predominantly reserved for when the primary TIPS is inaccessible or unfavourable for recanalization and for persisting portal hypertension despite verified patency on imaging. (Raissi et al 2019 ) It has demonstrated similar patency rates in the mid-term compared to TIPS of patients who do not undergo parallel TIPS. (Raissi et al 2019 ; Helmy et al 2006 )…”
Section: Discussionmentioning
confidence: 99%
“…(Dabos et al 1998 ) Parallel TIPS has since been predominantly reserved for when the primary TIPS is inaccessible or unfavourable for recanalization and for persisting portal hypertension despite verified patency on imaging. (Raissi et al 2019 ) It has demonstrated similar patency rates in the mid-term compared to TIPS of patients who do not undergo parallel TIPS. (Raissi et al 2019 ; Helmy et al 2006 )…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that following the previously mentioned studies, one publication of case series and limited case report studies were published [20][21][22]. Luo et al reported the outcome of 18 patients with portal hypertension with PS insertion.…”
Section: Discussionmentioning
confidence: 99%
“…7 In 1992, Haskal et al first reported creation of a second parallel TIPS tract to reduce the portosystemic pressure gradient. 8 More recently, He et al 9 and Raissi et al 10 have also described the feasibility and effectiveness of parallel TIPS. Parallel TIPS involves the creation of a second new tract, usually from the right hepatic vein to the right branch of the portal vein, parallel to the first stent and using the first stent as a marker.…”
Section: Discussionmentioning
confidence: 99%
“…If not, then a combination of PTFE covered and uncovered stent can be used. 10 We describe a unique technique where in cases of TIPS/ DIPS revision a new tract can be created through a lateral direct puncture across the fenestrations of the existing dysfunctioning stent graft. This technique can be used when it is not possible to gain access into the proximal hepatic venous end of the blocked stent.…”
Section: Discussionmentioning
confidence: 99%